Some Remarks About Negative Efficiencies in DEA Models - Gomes, Eliane Gonçalves; Mello, João Carlos C. B. Soares de; Meza, Lidia Angulo; Silveira, Juliana Quintanilha da; Neto, Luiz Biondi; Abreu, Urbano Gomes Pinto de (IntechOpen, 2012)
None